2022
DOI: 10.1001/jamanetworkopen.2022.22966
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Severe Maternal Morbidity in the US Across the Transition to ICD-10-CM/PCS From 2012-2019

Abstract: Key Points Question How did US rates of severe maternal morbidity (SMM), overall and by SMM indicator and state, change from 2012 to 2019 across the transition to International Classification of Diseases, Tenth Revision, Clinical Modification/Procedure Coding System ( ICD-10-CM/PCS ) coding? Findings In this repeated cross-sectional analysis including 5.9 million delivery hospitalizations from 2012 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…Research has suggested trends of worsening maternal health associated with depression, substance use, and severe maternal morbidity in the US over the past decade. All-cause and drug/alcohol poisoning mortality rates for pregnant and recently pregnant women also increased in the US from 2015 to 2019 .…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested trends of worsening maternal health associated with depression, substance use, and severe maternal morbidity in the US over the past decade. All-cause and drug/alcohol poisoning mortality rates for pregnant and recently pregnant women also increased in the US from 2015 to 2019 .…”
Section: Introductionmentioning
confidence: 99%
“…The national rate without blood transfusions was 35 per 10,000 as compared with Georgia’s 2014 rate of 75.3 (95% CI: 70.1, 80.5) per 10,000. The upward trend of Georgia’s annual SMM rate parallels the upward trend of the overall US SMM rate over a similar timeframe 22,27. The 5 most common indicators of SMM in Georgia during the study timeframe were blood transfusion, disseminated intravascular coagulation, hysterectomy, adult respiratory distress syndrome, and acute renal failure.…”
Section: Discussionmentioning
confidence: 60%
“…The reduction of preventable SMM may also stem increasing maternal mortality rates because they share similar risk factors. 4 Prior examination of SMM using mainly administrative hospital data 5 demonstrated that approximately half of adverse maternal outcomes in the US are attributable to preventable harm or unintended consequences from clinical practice and system of delivering perinatal care. 6,7 The CDC, American College of Obstetricians and Gynecologists (ACOG), and Society for Maternal-Fetal Medicine (SMFM) recommend that birthing facilities routinely identify and review SMM events.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Such data, primarily collected for billing purposes, are prone to coding errors and lack clinical nuance needed for real-time, in-depth reviews to inform SMM prevention efforts. 5 , 9 , 13 In July 2020, the Maryland Maternal Health Innovation Program (MDMOM) piloted an SMM surveillance and review program working with 6 of the 32 birthing hospitals in Maryland, covering approximately one-quarter of the more than 60 000 births in the state annually. This initiative is a component of a series of interventions implemented in 2020 to reduce maternal mortality in Maryland.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation